Sound- and Pressure-Induced Vertigo Associated with Dehiscence of the Roof of the SuperiorSemicircular Canal - Mong, Andrew (AJNR Am J Neuroradiol, 1999)
Summary: In many types of peripheral vertigo, imaging is not part of the initial evaluation. We present a patient with sound- and pressure-induced vertigo associated with bony dehiscence of the roof of the superior semicircular canal. The diagnosis of this new entity can only be made by high-resolution coronal CT imaging of the temporal bones. In patients with this symptom complex, CT should be performed early in the diagnostic workup.